CARACTERIZACIÓN DE LA GAMMA GLOBULINA EN SALIVA Y EN SUERO EN LA EVOLUCIÓN DEL HIV (SIDA). - Taboada, Manuel (1998)
A Porcentage of the concentration of Inmunoglobulinas in total saliva and whey in a sample of healthy people between l8 and 35 years and 90 sick people of HIV in the phase II, III, IV between l8 and 45 years old. In the group of the control group was obtained, these values could be related with the measure of the sickness and with the symptomatology previous to each case.